Polytobacco usage and mental health among Malaysian secondary school-going adolescents: Findings from the national school-based study - Lim, Kuang Hock; Cheong, Yoon Ling; Lim, Jia Hui; Kee, Chee Cheong; Mohd Ghazali, Sumarni; Cheah, Yong Kang; Heng, Pei Pei; Marine, Ali Aman; Mat Hashim, Mohd Hazilas; Goh, Wei Wen; Lim, Hui Li (European Publishing, 2025)
INTRODUCTION The emergence of novel tobacco products has led to an increase in the consumption of diverse tobacco items among adolescents. The smoking habits of adolescents adversely affect their physical and emotional health. This study aimed to ascertain the prevalence of polytobacco use among Malaysian teenagers and to identify the mental health issues associated with dual or polytobacco use. METHODS This is a secondary dataset analysis of cross-sectional data from 27479 secondary school adolescents who participated in the 2017 Malaysian Adolescent School Health survey. The primary outcome of our study pertained to self-reported mental health characteristics (stress and depressive symptoms). The research used multivariable logistic regression analysis to assess the associations between the use of tobacco products and mental wellness. RESULTS Of the respondents, 79.9% were non-tobacco users, 9.2% were single tobacco users, 4.7% were dual tobacco users, and 7.3% were polytobacco users. Individuals engaged in polytobacco use exhibited elevated levels of stress (16.7%; p<0.001) and depression (33.7%; p<0.001) relative to those utilizing fewer tobacco products. Polytobacco product users exhibited a 1.64-fold (95% CI: 1.30–2.06) increased likelihood of reporting stress symptoms and a 1.75-fold (95% CI: 1.46–2.09) increased likelihood of reporting depression symptoms in comparison to non-tobacco users. CONCLUSIONS Adolescents who engage in dual or polytobacco use frequently experience internalized mental health issues, including symptoms of stress and despair. It is essential to perform early assessments of high-risk individuals, provide them with information regarding the importance of cessation, and implement proactive interventions for these groups' psychological challenges.